Implementation of Lavender Aromatherapy for Post-Caesarean Section Mothers Experiencing Acute Pain - Indahwati Ajiningwulan; Nurul Hayati; Musviro Musviro; Rizeki Dwi Fibriansari; Sri Wahyuningsih (KHD Production, 2025)
A Caesarean section is a surgical procedure through the abdominal wall and uterus to remove the fetus, which generally causes more severe postpartum pain than standard delivery. Pain due to surgery, if not immediately addressed, will hinder the mother's recovery process and the baby's breastfeeding process. One effort that can be done to reduce pain is with non-pharmacological methods, one of which is through the administration of lavender aromatherapy. This study aimed to explore the implementation of lavender aromatherapy administration for post-cesarean section mothers experiencing acute pain in the Lotus Room of Dr. Haryoto Lumajang Regional Hospital. The method used in this study was a case study involving one participant who met the inclusion criteria, namely a post-CS patient treated in the Lotus Room of Dr. Haryoto Lumajang Regional Hospital, exhibiting 5 out of 6 significant signs and symptoms of acute pain with a moderate to severe pain scale. Data was collected on March 18-20, 2025, using interviews, observation, and documentation techniques. The measurement instrument for the level of pain reduction was the Numeric Rating Scale (NRS) and the observation sheet for outcome criteria. Aromatherapy was implemented using a diffuser with five drops of lavender essential oil twice daily for 20 minutes. The study results showed a reduction in pain levels, with the following criteria: pain complaints decreased from 8 (severe) to 2 (mild), decreased grimacing, decreased anxiety, decreased protective behavior, improved pulse rate, and improved sleep quality. Pain management with one of the lavender aromatherapy interventions can reduce pain from 8 to 2 on NRS.